2022
DOI: 10.3389/fimmu.2022.864156
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation Pattern Predicts Prognosis and Indicates Tumor Microenvironment Infiltration Characterization in Bladder Cancer

Abstract: BackgroundSUMOylation is an important component of post-translational protein modifications (PTMs), and bladder cancer (BCa) is the ninth most common cancer around the world. But the comprehensive role of SUMOylation in shaping tumor microenvironment (TME) and influencing tumor clinicopathological features and also the prognosis of patients remains unclear.MethodsUsing the data downloaded from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO), we comprehensively evaluated the SUMOylation pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…In the meantime, four LUAD datasets, GSE13213, GSE31210, GSE68465, and GSE30219, were obtained from the Gene Expression Omnibus (GEO) database ( https://www.ncbi.nlm.nih.gov/geo/ ). Data from the five datasets were combined and normalized using the R software to eliminate potential batch effects ( Xia et al, 2022a ). Corresponding clinical data were also extracted, and samples with missing data of OS or exhibiting OS as 0 were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…In the meantime, four LUAD datasets, GSE13213, GSE31210, GSE68465, and GSE30219, were obtained from the Gene Expression Omnibus (GEO) database ( https://www.ncbi.nlm.nih.gov/geo/ ). Data from the five datasets were combined and normalized using the R software to eliminate potential batch effects ( Xia et al, 2022a ). Corresponding clinical data were also extracted, and samples with missing data of OS or exhibiting OS as 0 were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning-based unsupervised consensus was used to cluster 398 COAD patients in the TCGA cohort to explore the relationship between m7G-related DELs and COAD subtypes ( 16 , 18 ). By increasing the clustering variable (k) from 2 to 9, we found that when k =2, the within-group correlation was highest, whereas the between-group correlation was low ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Consensus clustering was performed using the ConsensuClusterPlus R package (16)(17)(18). The immune microenvironment of tumor tissue was evaluated using the estimate R package, and we calculated the evaluation scores of immune and stromal cells.…”
Section: Consensus Clustering and Its Immune Signaturementioning
confidence: 99%
“…The molecular classification of breast cancer played a vital role in the development of precise treatment and clinical practice ( Zhao et al, 2020 ). Another SUMOylation pattern could predict the prognosis and tumor microenvironment infiltration characterization in bladder cancer ( Xia et al, 2022b ). Moreover, Qi-Dong et al developed a ferroptosis pattern in bladder cancer that could guide the clinical therapeutic strategy ( Xia et al, 2022c ).…”
Section: Discussionmentioning
confidence: 99%